Influence of Substrate Modification with Dipole Monolayers on the Electrical Characteristics of Short-Channel Polymer Field-Effect Transistors - Takashi Nagase; Takeshi Hirose; Takashi Kobayashi; Rieko Ueda; Akira Otomo; Hiroyoshi Naito (Applied Sciences, 2018)
This study investigates the influence of self-assembled monolayer treatment of gate insulators on the electrical characteristics of bottom-gate/bottom-contact organic field-effect transistors (OFETs) with short channel lengths of 5 μm to 30 nm. The treatment of 3-chloropropyltrichlorosilane (CPTS) with large dipoles produces a high built-in electric field perpendicular to the SiO2 gate insulator surface, which results in a threshold voltage shift and enhanced hole injection compared to the treatment of phenethyltrichlorosilane (PETS) with small dipoles. Pronounced parabolic drain current‒voltage (ID‒VD) characteristics due to a space-charge limited current are observed in short-channel OFETs based on poly(3-hexylthiophene) with CPTS-treated gate insulators. CPTS treatment on short-channel OFETs based on poly(9,9-dioctylfluorene-co-bithiophene) (F8T2) suppresses the nonlinear ID increase in the low VD region caused by the voltage drop at the Au/F8T2 contact. The influence of the increase in the net source-drain electric field associated with the reduced voltage drops on the channel-length dependence of the field-effect mobility of short-channel F8T2 FETs is also discussed.